EU data protection reform: Opportunities and concerns - Alexander Dix; Gregor Thüsing; Johannes Traut; Laurits Christensen; Federico Etro; Susan Ariel Aaronson; Rob Maxim (Intereconomics, 2013)
Last year, the European Commission proposed a comprehensive reform of the EU's data protection rules. The proposed regulation has been surrounded by fierce controversy and has been the subject of frenzied lobbying by global corporations, industry groups, research centres and privacy campaigners on both sides of the Atlantic. This Forum applies cool economic reasoning to this heated issue. What are the potential economic benefits of EU harmonisation? Will the proposed regulation negatively impact the competitiveness and innovation of European firms in the global marketplace? Or could it jeopardise attempts to protect privacy as a fundamental right in civil societies?
Keywords: 330; Datenschutz; EU-Recht; Reform; Cloud Computing; Digitale Güter; EU-Staaten